Hedging devices in translation of Ghassan Kanafani’s novel "Rijalun fi ash-shams” - Alsemeiri, Ibrahim M. I.; Abufayyad, Fawzi Ibrahim; Hamawiya, Adham (2021)
This study is essentially projected to explore the process of translating hedges existed in Arabic language novel of Gassan Kanafni’s ( "رجال في الشمس" ( 1962 “Rijolun fo Ash-shamsi” into English language in “Men in the Sun” of Hilary Klipatrick (1978). It investigates how the hedges forms and types are affected by many factors especially the cross-cultural and linguistic system factors after the translation process and it may convey more commitment or less according to the language culture and system. The collected data includes the whole novel which consist of seven chapters in both versions. In this research, there were two main objectives have been proposed. The first objective is to find out how the degree commitment as a major hedging marker in this Arabic novel is affected by the English translation. The second objective aims to structure the first Arabic hedging taxonomy. Hyland’s typology (1998) is used in order to collect the data from both versions. The researchers collect the hedges forms from English first then, they translated all these forms into Arabic language and after that they stared to look for hedges forms according to English taxonomy of Hyland’s typology (1998). The findings of the study show that: firstly, the culture has affected the degree of commitment and the range numbers of hedges. There are more hedges in English novel than Arabic one. The cross-cultural factors have affected the hedges forms after the translation because the English readers or audience could not understand the degree of commitment. Arab culture is using hedges, but they still have a high degree of responsibility or commitment of their words. Finally, this study proposed the first taxonomy or classification in Arabic language by the researcher Ibrahim Alsemeiri with the assistant of Professor Fawzi Abufayyad of Islamic university in Gaza, which tackles with hedges forms and it is considered as contribution from this study.